PELATIHAN DAN PENDAMPINGAN PENGUNAAN GOOGLE FORM, GOOGLE CLASSROOM, DAN POWER POINT PADA GURU MTSN 6 BIREUEN - Kiramim Bararah; Parulian Akbar Hutagalung (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Technological advances are not something to worry about or concern about, teachers must take part in the uncontrollable development of technology to succeed in the implementation of the teaching and learning process. This research aims to provide training to teachers at MTsN 6 Bireuen on how to use google forms, google classes, and PPT so that they can be applied in the implementation of learning. This research uses a qualitative approach by going and meeting directly with the research subject. Data were collected through observation and documentation, then analyzed through three steps, namely data reduction, data presentation and conclusion drawing. The results showed that teachers were very interested in training on the utilization of google forms, google classroom, and PPT, because it can facilitate teachers in carrying out all learning activities, such as giving assignments, conducting surveys, preparing teaching materials, and others. This activity is limited because it is only conducted in three days. Further research can continue with the same software, but with more in-depth and thorough training.